Decrypting the Central Mystery of Quantum Mathematics:: Part 4. In What Medium Do Elementary Waves Travel? - Boyd, Jeffrey (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
We live in a world, half of which consists of invisible elementary waves, of which we know very little. They are not electromagnetic waves: they travel in the opposite direction and convey no energy. What is the medium in which they travel? Franco Selleri (1936-2013) of University of Bari, Italy, devoted his career to answering that question. He developed his own theory of relativity. Zero energy quantum waves travel in Lorentz aether at rest. His relativity differs from Einstein’s Theory of Special Relativity (TSR) in terms of Absolute Simultaneity. If two events are simultaneous for one observer, they are simultaneous for all observers. Although this contradicts TSR, international treaties have adopted Absolute Simultaneity as the basis for coordinating all atomic clocks to the nanosecond. Atomic clocks control all other clocks. Absolute simultaneity is essential for commerce and computer networks.. Selleri’s relativity can be divided into two parts: time and aether. Time can be understood without ever speaking of the speed of light. When it comes to aether, a subject rarely mentioned today, it appears to be Isaac Newton’s absolute time and space, modified to fit the Lorentz transformations and the non-Euclidean curved space of Einstein’s General Relativity.